Studi probabilitas transmisi dan karakteristik IV pada molekul DNA G4 - Refpo Rahman; Efta Yudiarsah (University of Bengkulu, 2020)
[The study of transmission probability and IV chracteristics of a G4 molecule] In this era, there have been many theoretical and experimental studies conducted to enhance technological development. The development of technology continues to grow rapidly with electronic components that are getting smaller towards nano. Nanotechnology is becoming increasingly interesting because it can be created through DNA that is found in either the human body or other living things. This research was conducted to study DNA transport properties by calculating transmission probabilities and I-V characteristics. The DNA studied is DNA that has been modified consisting of 4 guanine bases arranged stacked to form a square called G4-DNA. G4-DNA is composed by having 32 base pairs and connected by electrodes at the end. The transport properties of G4-DNA were studied using the Hamiltonian tight binding approach. Transmission probability is calculated using the method of the Green Function Hamiltonian to determine the possibility of electrons flowing along the DNA pathway. This transmission probability is used in determining the I-V Characteristics based on the Landauer Büttiker formula. The results are obtained that the electron transport process along the G4-DNA molecule is an increase in current to high voltage. The effects of I-V characteristics are seen by affecting the twisting motion frequency up to 5.12 meV which is a significant increase in current. The results of this study can provide information about the characteristics of DNA that can be applied in the future in manufacture of nanotechnology device.